Common Variants for Heart Failure - Shen, Shutong; Tao, Lichan; Wang, Xiuzhi; Kong, Xiangqing; Li, Xinli (Current Genomics, 2015)
Heart failure (HF) is a common disease with high morbidity and mortality; however, none of the drugs available are now entirely optimal for the treatment of HF. In addition to various clinical diseases and environment influences, genetic factors also contribute to the development and progression of HF. Identifying the common variants for HF by genome-wide association studies will facilitate the understanding of pathophysiological mechanisms underlying HF. This review summarizes the recently identified common variants for HF risk and outcome and discusses their implications for the clinic therapy.
Keywords: Genome-wide association studies